2019
DOI: 10.3389/fnins.2018.01050
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Synergy Alteration of Human During Walking With Lower Limb Exoskeleton

Abstract: Muscle synergy reflects inherent coordination patterns of muscle groups as the human body finishes required movements. It may be still unknown whether the original muscle synergy of subjects may alter or not when exoskeletons are put on during their normal walking activities. This paper reports experimental results and presents analysis on muscle synergy from 17 able-bodied subjects with and without lower-limb exoskeletons when they performed normal walking tasks. The electromyography (EMG) signals of the tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…According to Sylos-Labini et al ( 2014 ), the assistive forces provided by an exoskeleton may result in a change of the muscle coordination manners (i.e., muscle synergies). Similar conclusions were also given by the related studies that investigated the effect of robotic gait assistance on the muscle function of the subjects (Moreno et al, 2013 ; Li et al, 2019 ). The altered muscle functions would cause an unknown distribution change of sEMG, therefore cause adverse effects on the sEMG-based motion-decoding methods.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…According to Sylos-Labini et al ( 2014 ), the assistive forces provided by an exoskeleton may result in a change of the muscle coordination manners (i.e., muscle synergies). Similar conclusions were also given by the related studies that investigated the effect of robotic gait assistance on the muscle function of the subjects (Moreno et al, 2013 ; Li et al, 2019 ). The altered muscle functions would cause an unknown distribution change of sEMG, therefore cause adverse effects on the sEMG-based motion-decoding methods.…”
Section: Introductionsupporting
confidence: 83%
“…How the exoskeletons affect the muscle functions of the subjects have been investigated for many years (Steele et al, 2017 ). Prior studies have revealed that external forces that were provided by the exoskeletons would alter the activity-level and recruitment patterns of the muscle groups (Sylos-Labini et al, 2014 ; Li et al, 2019 ). The study (Sylos-Labini et al, 2014 ) recorded the sEMG activity of six healthy individuals during overground walking with a lower-limb exoskeleton.…”
Section: Related Workmentioning
confidence: 99%
“…These regularities are called “muscle synergies”. The limb movements are accomplished by activating these synergies coordinately [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since it is quite difficult to measure multiple joint torques and ground reaction forces simultaneously for the human-exoskeleton system, employing gait data acquired by motion capture devices is more convenient for the control system to process and configure [7]. Due to different influence factors such as subjects' biomechanics and physiological movement diversity, gait kinematic signals can be still characterized as nonlinear and nonstationary signals [8].…”
Section: Introductionmentioning
confidence: 99%